Frequent estuarine engineering exacerbates flood risk in the Greater Bay Area - Ping Zhang; Haichen Liu; Huayang Cai; Suying Ou; Zhijun Dai; Jianliang Lin; Qingshu Yang (Engineering Applications of Computational Fluid Mechanics, 2025)
Global mega-bay systems are experiencing intensive estuarine engineering (e.g. dredging and reclamation), yet the compound effects and underlying mechanisms driving flood risk amplification remain insufficiently quantified. This study investigates flood risk changes in the Bay-Inlet-Channel system of China’s Greater Bay Area (ranked as the world's fourth largest mega-bay) through extreme value analysis of 1965–2017 water level records using generalized extreme value (GEV) theory and max-stable process modelling. Our results demonstrate spatially heterogeneity in flood risk trends, with differential extreme water level rise changes: 0.22 cm/yr at the bay mouth, 0.65 cm/yr in the inner bay, and 0.56 cm/yr in the upper tidal reach (Shiziyang), coinciding with a risk escalation from Category II (strong) to Category I (extreme). Hydrodynamic analysis reveals that deposition-induced tidal range attenuation at the bay mouth partially moderates flood risk acceleration, whereas synergistic effects of erosional dredging and convergent reclamation amplify both tidal and surge dynamics, consequently exacerbating flood risk in the inner bay, with the tidal reach exhibiting intermediate trends due to energy dissipation through Humen Inlet. Numerical simulations quantify maximum impacts on extreme high water levels, with 9.61% rising associated with slower-propagating waves from reclamation and 3.33% decreased with faster-propagating waves induced by dredging. Projections under SSP5-8.5 sea-level rise scenarios indicate that extreme high water levels will surpass optimized 300-yr return levels defense standards by 2080 (outer bay), 2090 (inner bay), and 2100 (tidal reach). These findings provide critical insights into global flood risk management in engineered mega-bay systems and advance methodological frameworks for extreme water level assessment.